Design Key Management System for DLMS/COSEM Standard-based Smart Metering - Hwan Ju, Seung; Suk Seo, Hee (International Journal of Engineering and Technology, 2018)
Background/Objectives: Security features are an essential part of recent smart metering systems. Smart meters are considered an important facility that must be protected by applying the latest security technologies.Methods/Statistical analysis: Security context determines the rules for applying/verifying security. DLMS/COSEM have Security suite to set of cryptographic algorithms. This is based on symmetric key based cryptographic communication. The high level security requires public key based cryptographic communication and digital signature.The security specification references the key scheme of DLMS-COSEM, which is based on a single set of unique symmetric keys per meter.Findings: we have studied a sequence for distributing security keys required by DLMS / COSEM.Our smart metering key distribution system can provide a security key management system such as key generation / distribution between AMI components. This is a PKI-based authentication using public key method (ECC), and a DLMS standard key distribution method after generating a session key using a public key. This system can also provide a key management scheme between DLMS clients not defined in the DLMS standard.Improvements/Applications: we analyze security requirements of DLMS/COSEM for secure smart metering and design key distribution/management method.Â Â